On single measurement stability for the fractional Calderón problem - Rüland, Angkana (SIAM journal on mathematical analysis, 2021)
In this short article we complement the known single measurement uniqueness result for the fractional Calderón problem by a single measurement logarithmic stability estimate. To this end, we combine quantitative propagation of smallness results for the Caffarelli--Silvestre extension and a boundary doubling estimate. The latter yields control of the order of vanishing of solutions to the fractional Schrödinger equation and provides the central step in passing from the quantitative unique continuation for solutions to the logarithmic stability of the potential $q$.